“Moving Past Time Itself to See Changes Happen”: Faculty Interview with Dominic Walker - Sun, Shannon (Columbia Undergraduate Research Journal, 2017)
On the corner of Dominic Walker’s desk lies a neat stack of books. Juxtaposed against each other, two of the titles read, “Best of the Best” and “Unequal Childhoods.” These books, decorative elements on an otherwise barren desktop, were a humble display of the larger questions that occupied Walker’s academic research and personal life. At age 26, Walker, a Ph.D. candidate in Sociology at Columbia University, is pursuing research on the interwoven systems of privilege that give rise to inequality. Originally from Baltimore, Maryland, Walker draws extensive inspiration from his upbringing in drastically different school systems. Growing up in a single-parent household, Walker first attended a public elementary school in Baltimore, earned a sponsorship to an all-boys Catholic middle school, and then left home to attend a prestigious, all-boys boarding high school in Virginia. With each move, Walker became more acutely aware of the reason for his departure.